2010
DOI: 10.1016/j.ydbio.2009.11.022
|View full text |Cite
|
Sign up to set email alerts
|

The proprioceptive and contractile systems in Drosophila are both patterned by the EGR family transcription factor Stripe

Abstract: Coordinated locomotion of Drosophila larvae depends on accurate patterning and stable attachment to the cuticle of both muscles and proprioceptors (chordotonal organs). Unlike muscle spindles in mammals, the fly chordotonal organs are not embedded in the body-wall muscles. Yet, the contractile system (muscles and tendons) and the chordotonal organs constitute two parts of a single functional unit that controls locomotion, and thus must be patterned in full coordination. It is not known how such coordination is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 41 publications
0
32
0
Order By: Relevance
“…Although ch organs reach their basic final shape and position at stage 15, further refinement occurs during later stages, at the time when ATK expression peaks (Carlson et al 1997b;Inbal et al 2003;Kraut and Zinn 2004;Hartenstein 2005). Several studies suggest the importance of the accessory cells in this final process of organ refinement: in the v'ch1 chordotonal organ (Mrkusich et al 2010), the positioning of the growing ciliary dendrite has shown to result from pulling forces that the dorsally extending cap cell exerts on the dendrite tip; and in the lch5 organ, the interaction between ligament and ligament attachment cells ventrally straightens the whole organ (Inbal et al 2004;Klein et al 2010). Thus, to ensure proper spatial and temporal transmission of the morphogenetic forces, the different components of the sensillum must interact adequately.…”
Section: Atk Is An Ecm Protein Implicated In the Late Morphogenesis Omentioning
confidence: 99%
“…Although ch organs reach their basic final shape and position at stage 15, further refinement occurs during later stages, at the time when ATK expression peaks (Carlson et al 1997b;Inbal et al 2003;Kraut and Zinn 2004;Hartenstein 2005). Several studies suggest the importance of the accessory cells in this final process of organ refinement: in the v'ch1 chordotonal organ (Mrkusich et al 2010), the positioning of the growing ciliary dendrite has shown to result from pulling forces that the dorsally extending cap cell exerts on the dendrite tip; and in the lch5 organ, the interaction between ligament and ligament attachment cells ventrally straightens the whole organ (Inbal et al 2004;Klein et al 2010). Thus, to ensure proper spatial and temporal transmission of the morphogenetic forces, the different components of the sensillum must interact adequately.…”
Section: Atk Is An Ecm Protein Implicated In the Late Morphogenesis Omentioning
confidence: 99%
“…Although Stripe is not involved in the initial steps of cap-ChO-attachment cells (Klein et al, 2010).…”
Section: Attachment Of Chordotonal Organs To Ectodermal Attachment Cementioning
confidence: 99%
“…The fact that the identity and differentiation of both types of attachment cells (tendons and ChO attachment) is determined by Stripe expression, raises the question as to what distinguishes between these two developmental programs. Although a specific cell-identity regulator has not been identified, ectopic expression of Stripe in the ectoderm reveals domains that are competent to differentiate as tendon cells (expressing the common attachment cell markers, but are devoid of alphaTub85E; Klein et al, 2010) and domains that are competent to differentiate as ChO attachment cells (expressing the common attachment cell markers as well as alpha-Tub85E). This observation suggests that the epidermis is not equipotent in its response to Stripe expression and that the competence of cells to acquire one of the two attachment cell-identities (muscle attachment or ChO attachment) is embedded within the pre-patterned ectoderm and depends on segment polarity pre-pattern genes such as hh, en and wg.…”
Section: Force Transmitting Mechanisms and Their Developmental Role Imentioning
confidence: 99%
“…The development of larval ChOs during embryogenesis has been studied extensively 10,11,13,15,16 . The centerpiece of each ChO is a sensory unit composed of a neuron and a scolopale cell.…”
Section: Introductionmentioning
confidence: 99%
“…First, the larval ChOs develop during embryogenesis. Then, the adult ChOs start to develop in the larval imaginal discs and continue to differentiate during metamorphosis.The development of larval ChOs during embryogenesis has been studied extensively 10,11,13,15,16 . The centerpiece of each ChO is a sensory unit composed of a neuron and a scolopale cell.…”
mentioning
confidence: 99%